2016
DOI: 10.2174/1745017901612010001
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Carotid Atherosclerosis: The Role of Co-morbid Mood Disorders

Abstract: Introduction/Objective:To study in severe carotid atherosclerosis (CA): the frequency of mood disorders (MD); the impairment of quality of life (QoL); the role of co-morbid MD in such impairment.Methods:Case-control study. Cases: consecutive in-patients with CA (stenosis ≥ 50%). Controls: subjects with no diagnosis of CA randomized from a database of a community survey. Psychiatric diagnosis according to DSM-IV made by clinicians and semi-structured interview, QoL measured by the Short Form Health Survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…These prevalence estimates’ discrepancy could be attributed to the different methods and designs used in the included studies, such as the different tools for assessing depression. However, these studies, as well as our study, reported a high prevalence of depressive symptoms among CAD patients that ranged between 17% and 53% [ 33 - 43 ].…”
Section: Discussionmentioning
confidence: 64%
“…These prevalence estimates’ discrepancy could be attributed to the different methods and designs used in the included studies, such as the different tools for assessing depression. However, these studies, as well as our study, reported a high prevalence of depressive symptoms among CAD patients that ranged between 17% and 53% [ 33 - 43 ].…”
Section: Discussionmentioning
confidence: 64%
“…In these bioprocesses, T. gondii tachyzoites become an additional source of TgACAT1 and TgACAT2 and cathepsin proteases that are superimposing on the respective enzymes produced in the host vascular endothelial cells, thereby enhancing their final activities. These findings may be supported by at least six facts: (a) early stages of atherosclerosis began already in early embryonic life probably caused by congenital toxoplasmosis acquired in the first trimester of gestation as a result of parasite transmission from mother to fetus [110] ; (b) the parasite penetrated nucleated erythroblasts and macroreticulocytes from fetal mouse liver and the circulating erythrocytes of fetal mice [414] , and multiplied in the immature cells [812] ; (c) the accelerated atherosclerotic development was due to the increased levels of cholesterol and LDL reported in T. gondii infected humans [16] and animals [813] ; (d) the highest amongst analyzed regression coefficients (B = 12.49, p = 0.026, Eta 2 = 0.058) between the prevalence of toxoplasmosis and cardiovascular (cerebrovascular and ischemic heart) diseases in a set of 88 countries [30] ; (e) there is a frequent comorbidity of severe carotid atherosclerosis and mood disorders (p < 0.0001) [814] as well as a significant relationship between chronic T. gondii infection and mood disturbances [815] ; and (f) pravastatin, simvastatin and other statins (drugs with hypocholesterolemic and antiatherosclerotic activities) inhibited the adhesion, replication and proliferation of T. gondii [816][817][818][819] ; propranolol, a β-adrenoreceptor blocking agent, also exerted antitoxoplasmic Table 30 Effects of 1,25-dihydroxyvitamin D3 on innate immune system (acc. to Pelajo et al [786] ; Youssef et al [787] ; with own modification).…”
Section: Discussionmentioning
confidence: 98%
“…This data supports the hypothesis that MDQ positivity, by itself, identifies a condition of clinical interest regardless of comorbidity with other disorders. The dimensions explored by the SF-12 (albeit from a subjective perspective) include physical health and functioning, physical pain, vitality, social functioning, emotional condition, and 18 29.5 ± 7.3 7.0 ± 3.5 (N = 201) df 1,238 F = 9.937 p = 0.002 Wilson's disease 19 33.8 ± 9.0 4.4 ± 1.7 (N = 23) df 1,60 F = 0.344 p < 0.568 Carotid atheriosclerosis 20 30.6 ± 8.1 6.2 ± 5.0 (N = 46) df 1,83 F = 1.040 p = 0.311 Major depressive disorder 21 33.8 ± 9.2 5.6 ± 3.6 (N = 37) df 1,73 F = 2.66 p = 0.608 Eating disorders 15 34.0 ± 6.2 4.4 ± 6.6 (N = 60) df 1,97 F = 10.272 p = 0.603 Panic disorders 27 35.5 ± 4.6 2.9 ± 0.9 (N = 123) df 1,160 F = 19.454 p < 0.0001 Obsessive compulsive disorder 22 35.4 ± 6.9 2.9 ± 6.0 (N = 88) df 1,125 F = 3.709 p = 0.056 Post-traumatic stress disorder 23 36.3 ± 6.1 3.9 ± 1.0 (N = 26) df 1,91 F = 1.388 p = 0.243 Simple phobia 28 35.8 ± 6.1 2.5 ± 2.4 (N = 54) df 1,66 F = 10.016 p = 0.002 Agoraphobia 24 35. psychosocial disability. Therefore, these elements are not negligible on a clinical level.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some elements, such as the attitude of hyperactivity, typical of bipolar disorder, can be found in people who do not suffer from this disorder in specific conditions of conflict or social danger, 32 and a high frequency of a genetic variant (the allele RS1006737 of the CACNA1C gene considered a risk factor for bipolar disorder) was found in elderly people with hyperactivity/novelty-seeking traits but who are perfectly socially integrated and without any psychiatric diagnosis. [33][34][35] In this framework, even admitting that the presence of the "at-risk variant" may be found also in the not-at-risk subgroup, this cannot cancel a possible BD-genetic variant association relationship but certainly cannot justify a 18 2.9 ± 7.4 0.004 (1, 208) 0.948 Fibromyalgia 29 4.77 ± 5.76 0.975 (1,78) 0.327 Wilson disease 19 3.2 ± 7.9 0.027 (1,23) 0.072 Celiac disease 17 3.4 ± 5.4 0.119 (1,67) 0.732 Carotidal atherosclerosis 20 3.4 ± 8.2 0.052 (1,53) 0.821 MDQ positivity 2.73 ± 2.44 Pivot linear correlation. An indirect confirmation of a possible interaction between other risk factors than the genetic variant RS1006737 of the CACNA1C gene comes from a study that had to compare the score of MDQ and the presence of the above-cited genetic variant as screeners of BD, against a diagnosis of bipolar disorder carried out by clinicians as the Gold Standard.…”
Section: Discussionmentioning
confidence: 99%